2002
DOI: 10.1111/j.1151-2916.2002.tb00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Grain‐Boundary Effect on Electrical Properties of Gadolinium‐Doped Ceria

Abstract: The microstructural evolution and grain‐boundary influence on electrical properties of Ce0.90Gd0.10O1.95 were studied. The nanoscale powders synthesized from a semibatch reactor exhibited 50% green density and 92% sintering density at 1200°C (∼200°C lower than previous studies). Impedance spectra as a function of temperature and grain size were analyzed. The Ce0.90Gd0.10O1.95 with finest grain size possessed highest overall grain‐boundary resistance; this contribution was eliminated at temperatures >600°C, reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
48
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 13 publications
11
48
1
Order By: Relevance
“…It is inferred that the higher activation energy and lower total conductivity at T < 400 • C is due to the larger grain boundary area and consequently the higher grain boundary resistivity of the 1200 • C sample. Zhou et al have shown that grain boundary resistivity in CGO10 becomes neglectable at temperatures >600 • C [26]. The effect of grain size can therefore only be detected at low temperatures.…”
Section: Resultsmentioning
confidence: 97%
“…It is inferred that the higher activation energy and lower total conductivity at T < 400 • C is due to the larger grain boundary area and consequently the higher grain boundary resistivity of the 1200 • C sample. Zhou et al have shown that grain boundary resistivity in CGO10 becomes neglectable at temperatures >600 • C [26]. The effect of grain size can therefore only be detected at low temperatures.…”
Section: Resultsmentioning
confidence: 97%
“…Experimental conditions always imply the presence of different 1D (e.g., dislocations) and 2D (e.g., grain boundaries) defects, which substantially reduces the conductivity. In particular, [20], Zhu et al [21], and Zhou et al [22]. All the experimental data are for 10 at.…”
Section: E Temperature Dependence Of Conductivitymentioning
confidence: 99%
“…Since GDC is almost eight times more expensive than undoped-CeO 2 , this could be an efficient approach to realize intermediate-temperature SOFCs. However, the hydrogen reduction reaction also occurs at the ASL and the oxygen ion conductivity of CeO 2 is lower than that of GDC; the catalytic properties of undoped-CeO 2 thus need to be enhanced [18,19]. Moreover, there are studies referring that when the ionic conductivity of the oxide material in anode layer was improved, the cell showed enhanced performance in anode side [20].…”
Section: Introductionmentioning
confidence: 91%